Corrosion behavior of X65 steel in CO2-saturated oil/water environment of gathering and transportation pipeline. Issue 5 (2nd September 2019) - Cheng, Yuanpeng; Bai, Yu; Tang, Shanfa; Zheng, Dukui; Li, Zili; Liu, JianGuo
Abstract : Purpose: The purpose of this paper is to investigate the corrosion behavior of X65 steel in the CO2 -saturated oil/water environment using mass loss method, potentiodynamic polarization technique and characterization of the corroded surface techniques. Design/methodology/approach: The weight loss analysis, electrochemical study and surface investigation were carried out on X65 steel that had been immersed in the CO2 /oil/water corrosive medium to understand the corrosion behavior of gathering and transportation pipeline steel. The weight loss tests were carried out in a 3 L autoclave, and effects of water cut and temperature on the CO2 corrosion rate of X65 steel were studied. Electrochemical studies were carried out in a three-electrode electrochemical cell with the test temperature was 60°C, and the CO2 partial pressure was 1 atm by recording open circuit potential/time and potentiodynamic polarization characteristics. The surface and cross-sectional morphologies of corrosion product scales were characterized using scanning electron microscopy. The phases of corrosion product scales were investigated using x-ray diffraction. Findings: The results showed that due to the wetting and adsorption of crude oil, the corrosion morphology of X65 steel changed under different water cuts. When the water cut of crude oil was 40-50 per cent, uniform corrosion occurred on the steel surface, accompanied by local pitting. While the water cut was 70-80 per cent, the resulting corrosion product scales were thick, loose and partial shedding caused platform corrosion. When the water cut was 90 per cent, the damaged area of platform corrosion was enlarged. Crude oil can hinder the corrosion scales from being dissolved by the corrosive medium, and change dimension and accumulation pattern of the crystal grain, thickness and structure of the corrosion scales. Under the corrosion inhibition effect of crude oil, the temperature sensitive point of X65 steel corrosion process moved to low temperature, appeared at about 50°C, lower corrosion rate interval was broadened and the corrosion resistance of X65 steel was enhanced. Originality/value: The results can be helpful in selecting the applicable corrosion inhibitors and targeted anti-corrosion measures for CO2 -saturated oil/water corrosive environment.